Factors influencing the outcomes of percutaneous coronary intervention in the stent era. (October 2012) - Prabhakar, Shashi K; Abbott, Jinnette Dawn
In the three decades following the performance of the first angioplasty by Andreas Gruentzig in 1977, the volume of percutaneous coronary interventions (PCIs) has exponentially increased. Our knowledge of the factors which influence PCI outcomes drove development of new techniques and technology, resulting in improved outcomes for patients. For example, the advent and advances in stents have significantly reduced acute procedural complications, and the incidence of restenosis and repeat revascularization procedures. In addition, developments in pharmacology have influenced ischemic complications and bleeding rates. Randomized controlled trials and registries have contributed to the wealth of data currently available and form the basis for the development of PCI guidelines. In general, factors that influence PCI outcomes include two broad categories: patient related encompassing clinical and anatomical and procedure related. A review of procedural and late PCI outcomes is presented, including identification of the main factors that have been associated with risk.